Implementation of the MBKM Curriculum (Independent Learning Independent Campus) Towards the Islamic Religious Education Study Program at Higher College Level - Khairatunnimah. SM; Reni Puspita Sari; Arifatus Solihah (International Journal of Educational Narratives, 2024)
Background. Universities have so far implemented a credit learning system which is almost entirely dependent on classroom learning. This shows the low level of learning independence for students. Therefore, the idea of “Independent Learning Independent Campus” emerged, or "MBKM", and is currently a program of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. Purpose. This research aims to describe the implementation of the MBKM curriculum in Islamic religious education study programs in higher education. Based on data obtained from the official Ministry of Education and Culture website, it shows the rapid growth of universities implementing the MBKM program, from 576 universities in 2022 to 921 universities in 2023, or an increase of 60% per year. Method. This type of research is library research. This research uses a content analysis method, namely a technique that identifies every word, sentence in a text or series of texts, concepts or themes. Meanwhile, the data sources used by researchers are books and research journals related to problem formulation. Results. The research results show that the MBKM curriculum (Independent Learning Independent Campus) is a new curriculum that is still hotly discussed in higher education circles. With the inauguration of MBKM, every university must prepare everything to support the success of the program. Several universities still face several obstacles in their implementation, as seen at UIN Walisongo and Unida Gontor. Conclusion. Thus, it is natural that every tertiary institution faces various difficulties in implementing MBKM. Therefore, universities must prepare well and hold outreach so that information can be widely accepted and understood by all parties, both lecturers and students.